ANALYSIS OF LIVER FUNCTION DISORDERS IN CRUMB RUBBER FACTORY WORKERS IN PALEMBANG CITY, SOUTH SUMATRA - Ferly Oktriyedi; Irfannuddin Irfannuddin; Ngudiantoro Ngudiantoro; Muhammad Hatta Dahlan (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Workers are required to receive Occupational Safety and Health protection. Work accidents can be influenced by physical, chemical, biological, ergonomic and psychological factors. Natural rubber factory is one of the industries that have risks to these factors. This study used a cross-sectional design. Data analysis used the CHAID (Chi-Square Automatic Interaction) method. P value < 0.05 was considered statistically significant. The results of the study showed that the average concentration of H2S in the air and in solids was above the quality standard and the average concentration of H2S in water was still below the quality standard. The average concentration of NH3 in water and in solids is above the quality standard and the average concentration of NH3 in the air is still below the quality standard. The results of the CHAID method analysis showed that glucose levels were associated with impaired liver function (p = 0.000; chi square = 48.766) and the risk of H2S exposure in the air with impaired liver function (p = 0.007; chi square = 7.944). In addition, 3 segments of liver function disorders were also found, namely Segment 1: Workers with abnormal BBS levels, high air exposure H2S; segment 2: Workers with abnormal glucose levels, low air exposure H2S; segment 3: Workers with normal glucose levels. Based on this segment, it was also found that the percentage of risk of experiencing liver function disorders were workers in segment 2 (36.3%) and segment 1 (17.4%).